Bilateral ovarian dysgerminoma with metastasis in female dog's mesenteric lymph node: a case report - Assis-Neto, Edgar Tavares de; Viana, Daniel de Araújo; Silva, Márcio César Vasconcelos (Brazilian Journal of Case Reports, 2021)
Dysgerminoma is a rare malignant neoplasm, associated with hormonal dysfunctions, which occurs in canine and feline females from middle age to elderly, without racial predisposition. In the present report, we described a case of ovarian dysgerminoma in a dog, only abdominal distension, persistent vulvar bloody discharge and apathy. The animal in question underwent exploratory laparotomy, where general neoformations were detected in the ovaries, and a lymph node with abnormal characteristics was also found. Therefore, surgery for ovariosalpingoisterectomy and puncture of a fragment of the lymph node altered for incisional biopsy was performed. The diagnosis was made through histopathological examination of the ovaries of the fragment derived from the lymph node, the result of which indicated the presence of dysgerminoma in both ovaries and in the lymph node, characterizing a metastasis. In view of this result, the chemotherapy protocol with the association of carboplatin and vinblastine was instituted, which proved to be effective and not very toxic to the animal, with no clinical sign of metastasis being identified after its use.